To withdraw futile treatment or to prolong life at all costs – an ethical point of view - Bołoz, Wojciech (Studia Ecologiae et Bioethicae, 2013)
Death is an inevitable phenomenon, but it can be experienced with dignity. For this reason, people are continually seeking decent ways to die. One of these is avoiding or moving away from so-called aggressive medical treatment if it doesn’t provide the dying with any therapeutic benefit and only generates costs and prolongs suffering. Consensual, inevitable death has been practiced in medicine since the time of Hippocrates, although at the same time we can see a tendency towards the opposite, uncompromising fight to the end. This trend is sometimes justified by the exceptional value of human life, which demands both the patient’s and doctor’s heroism. Since the Middle Ages, it has been a widely accepted practice to limit the care for human life to the use of so-called, ordinary, and proportionate remedies. The acceptance of this principle also means withdrawing futile therapy.